ChemInform Abstract: Methanesulfonic‐Acid‐Catalyzed Ring Opening and Glycosylation of 1, 2‐(Acetylcyclopropane)‐Annulated D‐Lyxofuranose. Issue 8 (February 2015) - Wang, Cong; Ma, Xiaofeng; Zhang, Jichao; Tang, Qin; Jiao, Wei; Shao, Huawu
Abstract The D‐lyxofuranose derivative (I) undergoes ring‐opening and subsequent glycosylation reaction with alcohols, thiols, and pyrimidines to give the corresponding glycosylation products with high diastereoselectivities.